Business Optimization Through Implementation of Cost of Production Pricing System Using Bill of Material Method - Yoga Sofian Ananta; Alzena Dona Sabilla; Agus Subhan Akbar (Komunitas Dosen Indonesia, 2025)
The furniture industry often struggles with setting accurate selling prices due to the lack of structured and precise cost calculation systems. Many furniture entrepreneurs still rely on traditional methods that base prices on market trends, without accounting for underlying production costs. This often leads to prices that are too low, eroding profit margins, or too high, making it difficult to stay competitive. This study introduces a novel Cost of Goods Manufactured (COGM) calculation system, integrated with the Bill of Materials (BOM) method, to advance current pricing systems in the furniture industry. By incorporating key cost elements such as raw materials, labor, and the impact of waste and rework, the system enhances the accuracy of COGM calculations. Additionally, it offers greater transparency by providing a detailed breakdown of each cost component, allowing entrepreneurs to better understand their production expenses. The implementation of this system led to a 15% improvement in pricing accuracy, significantly reducing pricing errors and optimizing production costs. Furthermore, businesses reported a 20% increase in competitiveness due to more informed pricing strategies. This research demonstrates that integrating COGM with BOM not only improves production efficiency but also strengthens pricing strategies, contributing to long-term profitability. It highlights the role of cost transparency in driving sustainable growth, particularly for small and medium-sized furniture enterprises.